Factores que determinan la competitividad de las PYMES exportadoras colombianas (2018)
The objective of the research is to analyze the key factors that determine the competitiveness of Colombian exporting SMEs. The identification of these factors is based on information obtained through a bibliographic review in a period of time between 2007 and 2017. The results demarcate the key factors depending on the level of the competitive context, such as the macroeconomic, sectorial and the microeconomic level, and each stage has key factors that influence the competitiveness of these firms.